A Simplified Method for Analyzing Overall Stability of Flexural-Type Braced Frame Structures - Shuwei Lan; Chi Xiao; Xu Chen; Chunhua Wang (Tehnički Vjesnik, 2023)
It is difficult to determine the effective length coefficient of weakly braced frame columns using the effective length coefficient method. When the stability of braced frame structures is calculated using the effective length coefficient method, it cannot reflect the effect of the brace on the frame, the mutual support of columns on the same floor, and vertical interactions between different floors, which is easy to lead to unreasonable design. In this study, based on a spring-rocking column model, the structural transformation concept was used to transform the second-order problem of determining the critical force of braced frame structures into a first-order problem of calculating the lateral stiffness of the structure. First, the repetitive frame element was used to obtain the lateral stiffness of each floor, and the second-order effect coefficient was used to determine the load stiffness of the floor. Next, the lateral stiffness and load stiffness of each floor was assembled. Finally, the principle in which the load stiffness reduces the lateral stiffness of the structure to zero when the braced frame structure buckles laterally were applied to derive a formula to directly calculate the critical force of the flexural-type brace frame structure. This formula reflects the interactions between the braced structure and the frame, the mutual support of columns on the same floor, and the vertical interactions between different floors. Therefore, it can compensate for the deficiency in which the criterion cannot calculate the critical force of braced frame structures and is suitable for quantitatively analyzing the vertical interactions between different floors of braced frame structures.